A strategic analysis of health behaviour change initiatives in Africa. Issue 1 (31st December 2023) - Mogo, Ebele R.I.; Shanawaz, Shaayini; Ademola-Popoola, Oreoluwa; Iqbal, Neelam; Aghedo, Osazemen; Ademola, Muili; Onyemaobi, Nnenna; Eniayewun, Aderayo; Ademusire, Babatunde; Adaramola, Tomiwa; Ugwu, Adaobi; Obi, Adaora; et al.
ABSTRACT: Background: Changed health behaviours can contribute significantly to improved health. Consequently, significant investments have been channelled towards health behaviour change initiatives in Africa. Health behaviour change initiatives that address social, economic and environmental levers for behaviour change can create more sustained impact. Objectives: Through a scoping study of the literature, we explored the literature on behaviour change initiatives in Africa, to assess their typologies. We explored whether the availability of initiatives reflected country demographic characteristics, namely life expectancy, gross domestic product (GDP), and population sizes. Finally, we assessed topical themes of interventions relative to frequent causes of mortality. Methods: We used the Behaviour Change Wheel intervention categories to categorise each paper into a typology of initiatives. Using Pearson's correlation coefficient, we explored whether there was a correlation between the number of initiatives implemented in a country in the specified period, and socio-demographic indicators, namely, GDP per capita, total GDP, population size, and life expectancy. Results: Almost 64% of African countries were represented in the identified initiatives. One in five initiatives was implemented in South Africa, while there was a dearth of literature from Central Africa and western parts of North Africa. There was a positive correlation between the number of initiatives and GDP per capita. Most initiatives focused on addressing sexually transmitted infections and were short-term trials and/or pilots. Most initiatives were downstream focused e.g. with education and training components, while upstream intervention types such as the use of incentives were under-explored. Conclusion: We call for more emphasis on initiatives that address contextual facilitators and barriers, integrate considerations for sustainable development, and consider intra-regional deprivation.